Chinese practical arts - Chong, Ah Kow (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
MLCC, in collaboration with Mandarin Unit of Foreign Languages Department, Centre for Modern Languages and Human Sciences, organizes Chinese Practical Arts classes for students currently attending UHF1111 Mandarin for Beginners and UHF2111 Intermediate Mandarin.